Über ganze Lösungen einer nach Gelfond-Leontjew verallgemeinerten Differentialgleichung von unendlich hoher Ordnung - Demtschenko, T. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Т. И. Демченко. Исследование разрешимости уравнения бесконечного порядка в обобщенных производных Гельфонда—Леонтьева в некотором классе целых функцийT. Demčenko. Begalinės eilės diferencialinės lygties, apibendrintos Gelfondo—Leontjevo prasme, sveiki sprendiniai